Sience Techno Park (STP) : Pelaksanaan Sistem Inovasi Daerah Provinsi Riau - Rizka Fitri Amriani; Panca Setyo Prihatin (UIR Press, 2019)
This research was conducted to find out the implementation of the Regional Innovation System Program (SIDa) at the Science Techno Park (STP) in Riau Province and to find out the inhibiting factors for the implementation of the Regional Innovation System Program (SIDa) in the Science Techno Park (STP) in Riau Province. Data collection techniques that the authors used in this study were observation, interview, and documentation techniques. Then the data analysis technique that the author uses in this study is descriptive quantitative. Based on the results of the research conducted by the author, the Implementation of the Regional Innovation System Program (SIDA) at the Sience Techno Park (STP) in Riau Province was sufficiently implemented. This shows that the Implementation of the Regional Innovation System Program (SIDA) at Sience Techno Park (STP) in Riau Province still needs improvement. There are several problems that hinder the Implementation of the Regional Innovation System Program (SIDA) at the Sience Techno Park (STP) in Riau Province, namely: 1) lack of experts to implement the program; 2) Not yet optimal participation of the community in the development of agriculture-based industrial clusters (Agro-industry); 3) weak community participation in increasing raw material production, so that the Sience Techno Park (STP) found it difficult to develop a network of innovation in fish, coconut and sago-based products.